Analisis Ketepatan Kode Diagnosis Ibu Bersalin Pasien Umum di Rumah Sakit Emhaka Tahun 2023-2024 - Maria Catherina Palar; Siswati, Siswati; Dina Sonia; Nanda Aula Rumana (Yayasan Literasi Sains Indonesia, 2025)
Coding in medical data and information processing is a process that transforms diagnosis into alphanumerical code based on The International Statistical Classification of Diseases and Related Health Problems (ICD). Validity is one of the coding quality elements that must be maintained. ICD codes for childbirth cases consist of maternal condition (O10-O75, O98-O99), methods of delivery (O80-O84), and outcome of delivery (Z37.-). This study aims to obtain an overview of the accuracy of maternal diagnosis codes for general patients at Emhaka Hospital Bekasi City in 2023 - 2024. The research method used is mixed methods with data collection techniques in the form of observation and interviews. From the 41 childbirth medical records that were analyzed, it was found that the percentage of inaccuracy of the mother's condition code was 75,61%, the delivery method code inaccuracy was 78,05%, and the outcome of delivery code inaccuracy was 65,85%. After analyzing the 5M management factors, the causes of code inaccuracy are the man, money, materials, and methods factors. It is necessary to update regulations used as a basis for making hospital policies, review, develop, evaluate and monitor existing SOPs, develop medical records officers through training, and review the distribution of officer workload.